PERANCANGAN INFOGRAFIS “BRAIN CARE”, TENTANG PERILAKU NEGATIF YANG DAPAT MERUSAK OTAK DALAM MEDIA MOTION GRAPHIC - FIRDAUS INDRA, Hendra Afriwan, S.Sn., M.Sn., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
The purpose of infographic design (1) to influence the public to avoid the negative behaviors that can damage the brain. 5W + 1H method used to solve this issue on the background and find solutions to these problems. (2) This infographic design will be delivered through the motion graphic. The role of motion graphicin infographic necessary to attract the audience, where the verbal message content can be presented in an attractive form of motion. The use of motion graphic containing audio and visual engaged thereby eliminating boredom when audience listening information on the infographic display.Keywords: infographic, brain, brain care, design method.